From quantity to quality: Delivering a home-based parenting intervention through China's family planning cadres - Sean Sylvia; Nele Warrinnier; Luo Renfu; Ai Yue; Orazio P. Attanasio; Alexis Medina; Scott Rozelle (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2018)
A key challenge in developing countries interested in providing early childhood development programs at scale is whether these programs can be effectively delivered through existing public service infrastructures. We present the results of a randomized experiment evaluating the effects of a home-based parenting program delivered by cadres in China's Family Planning Commission (FPC) - the former enforcers of the onechild policy. We find that the program significantly increased infant skill development after six months and that increased investments by caregivers alongside improvements in parenting skills were a major mechanism through which this occurred. Children who lagged behind in their cognitive development and received little parental investment at the onset of the intervention benefited most from the program. Household participation in the program was associated with the degree to which participants had a favorable view of the FPC, which also increased due to the program.
Keywords: J13; I21; I28; H11; 330; Early Childhood Development; Parenting; China; Poverty; Family Planning